Perancangan Mesin Penggulung Kumparan Transformator Berbasis Mikrokontroller Atmega8535 - Reinaldo Syas Gapita; Amir Hamzah; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Transformer is a tool to transfer electricity power inter two or more electricity circuit through electro magnetic induction. Transformer consist of two parts, they are primary and secondary part, every part consist of several coils with the certain number and zise. In the making transformer, rolling process is made repeatedly in order to reach the standarized transformer criteria it took time and effort hardly to reduce this impact. It is needed a tool which can rool fastly and automaticly. This tool used 200Vac motor and 1350 RPM speed as the roller, so that it can reach the source electric power and fast speed for autoprocess. It uses ATMEGA8535 microcontroller as the main cycle where the microcontroller receive the number of coil through keypad interface. Microcontroller controls the roller motor by comparing the coils numbers which is entered by the coil numbers processed by the motor. The coil number detection processed by ten magnetic sensor through statical magnet which was available on the shaft of the motor. Comparatorchanges the sensor output voltage into digital pulses. This digital were counted by the microcontroller where every ten pulses equal one coils is same with the input number, it means the microcontroller shut down the motor.Keywords: Transformer, Motor, ATMEGA8535, Magnetic sensor, Comparator.